2011
DOI: 10.1037/a0023452
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in combat-related stressors and their association with postdeployment mental health in a nationally representative sample of U.S. OEF/OIF veterans.

Abstract: Though the broader literature suggests that women may be more vulnerable to the effects of trauma exposure, most available studies on combat trauma have relied on samples in which women's combat exposure is limited and analyses that do not directly address gender differences in associations between combat exposure and postdeployment mental health. Female service members' increased exposure to combat in Afghanistan and Iraq provides a unique opportunity to evaluate gender differences in different dimensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
157
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(191 citation statements)
references
References 51 publications
28
157
4
Order By: Relevance
“…Women with combat exposure may be more likely than men to screen positive for PTSD [132,163] and depression [75,120]. However, this association is not shown for some groups [103,122,181]. Subsequent physical health and diagnoses may vary according to gender if deployment tasks differ for men and women.…”
Section: Healthmentioning
confidence: 99%
“…Women with combat exposure may be more likely than men to screen positive for PTSD [132,163] and depression [75,120]. However, this association is not shown for some groups [103,122,181]. Subsequent physical health and diagnoses may vary according to gender if deployment tasks differ for men and women.…”
Section: Healthmentioning
confidence: 99%
“…Military stressors include perceived threats and difficult living and working environments (Vogt, Samper, King, King, & Martin, 2008), as well as deployment stressors, lack of social support, and concerns about family disruptions (Vogt, Pless, King, & King, 2005). Many female and male veterans with combat exposure experience PTSD (Feczer & Bjorklund, 2009;Murdoch et al 2003;Vogt, Vaughn et al, 2011;Vogt et al, 2008). Further research demonstrates a high incidence (40%) of MST for females (Campbell & Raja, 2005;Haskell et al, 2010;Sadler, Booth, Mengeling, & Doebbeling 2004), and an association between MST and PTSD (Murdoch, Polusny, Hodges, & Cowper, 2006).…”
Section: Description Of the Problemmentioning
confidence: 99%
“…Some of these researchers failed to find gender differences in mental health problems occurring postdeployment, [7][8][9][10][11] but a few studies have found a higher incidence of PTSD in females returning from deployment compared with males, 12,13 who appear to have more substance abuse problems. 11 In some of these studies, female service members were also more likely than men to screen positive for depression.…”
mentioning
confidence: 99%
“…11 In some of these studies, female service members were also more likely than men to screen positive for depression. 7,8,11,[13][14][15] Greater psychologic morbidity has been seen in deployed military HCPs, explained by poorer group cohesion and traumatic military medical and postdeployment experiences. 16 Returning HCPs did not think that people understood what they had been through during deployment and felt unsupported.…”
mentioning
confidence: 99%